Institutional Ethnography as a Method of Inquiry: A Scoping Review - Malachowski, Cindy; Skorobohacz, Christina; Stasiulis, Elaine (Qualitative Sociology Review, 2017)
The purpose of this scoping review is to examine the extent, range, and nature of the use of institutional ethnography (IE) as a method of inquiry in peer-reviewed journal publications. Fifteen databases were searched between the years of 2003 and 2013. Relevant data were extracted from 179 included articles. Findings relate to nine key areas including year of publication, authorship and geography, types of journals, format of resources, authors’ descriptions of how they used IE, approaches used in conjunction with IE, data collection methods, standpoint, and institutional relations. Institutional ethnography was diversely conceptualized as: a (sociological) method of inquiry, methodology, research approach, feminist sociology, theory and methodology, framework, lens, field, perspective, and form of analysis. Inevitably, authors applied IE differently across their research and writing, ranging from direct usage or close adherence to IE in a comprehensive manner; to indirect usage or loose adherence to IE by drawing on it as inspiration, guidance, or influence; or borrowing from a certain facet of IE such as a particular theory, concept, method, tool, or analytic strategy. Additionally, some authors adapted IE to suit a specific purpose, which entailed using modified versions of IE to fit a given context or objective, while others strived to extend existing understandings of IE through critique, explanation, review, elaboration, or reflection. The results from this study are useful to both beginning and experienced institutional ethnographers, as the insights gained provide clarity about the use of IE, identify trends in its application, and raise additional questions.